Comparison of chemical compounds associated with sclerites from healthy and diseased sea fan corals (Gorgonia ventalina) - Toledo-Hernández, Carlos; Ruiz-Diaz, Claudia P.; Díaz-Vázquez, Liz M.; Santiago-Cárdenas, Vanessa; Rosario-Berrios, Derick N.; García-Almedina, Derek M.; Roberson, Loretta M. (PeerJ, 2017)
Background The roles of gorgonian sclerites as structural components and predator deterrents have been widely studied. Yet their role as barriers against microbes has only recently been investigated, and even less is known about the diversity and roles of the chemical compounds associated with sclerites. Methods Here, we examine the semi-volatile organic compound fraction (SVOCs) associated with sclerites from healthy and diseased Gorgonia ventalina sea fan corals to understand their possible role as a stress response or in defense of infection. We also measured the oxidative potential of compounds from diseased and healthy G. ventalina colonies. Results The results showed that sclerites harbor a great diversity of SVOCs. Overall, 70 compounds were identified, the majority of which are novel with unknown biological roles. The majority of SVOCs identified exhibit multiple immune-related roles including antimicrobial and radical scavenging functions. The free radical activity assays further confirmed the anti-oxidative potential of some these compounds. The anti-oxidative activity was, nonetheless, similar across sclerites regardless of the health condition of the colony, although sclerites from diseased sea fans display slightly higher anti-oxidative activity than the healthy ones. Discussion Sclerites harbor great SVOCs diversity, the majority of which are novel to sea fans or any other corals. Yet the scientific literature consulted showed that the roles of compounds found in sclerites vary from antioxidant to antimicrobial compounds. However, this study fell short in determine the origin of the SVOCs identified, undermining our capacity to determine the biological roles of the SVOCs on sclerites and sea fans.
Keywords: Gorgonia ventalina; Sclerites; Chemical defenses; Aspergillosis